Service Innovation for Customer Experience at the Bottom of the Pyramid - Sabherwal, Jasleen Kaur; Kaur, Kirandeep (Journal of Global Economy, Business and Finance, 2025)
This study explores the relationship between service innovation and customer experience in the context of a major Egyptian telecommunications company. It highlights the importance of customer-centric innovations in enhancing customer experience, especially in base-of-the-pyramid markets. The findings suggest that successful service innovations are those that address specific customer needs and provide value-for-money, convenience, and high service quality.